Ghumi Uttara: A New Music Creation | Ghumi Uttara: Sebuah Karya Musik Baru - Kadek Teddy Mertayasa; Kadek Suartaya (GHURNITA: Jurnal Seni Karawitan, 2022)
The creation of percussion music “Ghumi Uttara” raises the idea of creation that was born from the author's personal experience in playing percussion which identifies Buleleng Regency. This work highlights the processing of the sekatian and lelongoran percussions in Buleleng Regency. The aim is to give a message to the public that the percussion of the Sekatian and the percussion of the Lelongoran are percussions that identify Buleleng Regency which must be preserved and disseminated widely. The method used in the process of creating the musical creation "Ghumi Uttara", is the Panca Sthiti Ngawi Sani creation method from I Wayan Dibia in his book The Art Creation Methodology, which consists of the Inspiration Stage (ngewirasa), the Exploration Stage (Ngawacak), the Conception Stage ( Ngarencana), the execution stage (Ngewangun) and the production stage (Ngebah) from the five methods used in the process of creating this work are able to produce a creation of percussion music using the media, said Gamelan Gong Kebyar.  Ghumi Uttara's work uses a tri angga structure, namely kawitan/prefix (part I), pengawak/content (part II), pengecet/closing (part III), each of which has a different atmosphere or description, part I introduces the instruments used, in part II it depicts the Sekatian percussion in part II there is also a sekatian percussion motif from the sekatian form of lelongoran and sekatian form of pressing, while in part III it depicts the lelongoran percussion in this part III there are three lelongoran motifs. The creation of the creation of "Ghumi Uttara" percussion is expected to provide motivation for the younger generation to create works that not only cultivate traditional patterns but who are able to develop traditional patterns.